Crossroads of competition China, Russia, and the United States in the Middle East - Wasser, Becca; Shatz, Howard J. 1960-; Drennan, John; Scobell, Andrew; Carlson, Brian G.; Crane, Yvonne K. (RAND Corporation, 2022)
"Although U.S. strategic competition with China and Russia is largely focused on efforts in Asia and Europe, this competition will play out in other regions, including in the Middle East. This report details the political, economic, and military interests and activities of China and Russia in the Middle East, and identifies where those efforts contest, intersect, or complement U.S. interests and activities. The authors systematically identify the dimensions and locations in which strategic competition is occurring, where it is most likely to take place in the future, and where and how it is most likely to threaten U.S. interests. They provide recommendations for the steps that U.S. policymakers might take to maintain an advantageous position in the region and in strategic competition with China and Russia."--Publisher's description
Keywords: Strategie; Geopolitik; Internationale Politik; Regionalentwicklung; Politischer Prozess; Naher Osten; China; USA; Russland; Mittlerer Osten; Competition, International; China / Foreign relations / Middle East; Middle East / Foreign relations / China; United States / Foreign relations / Middle East; Middle East / Foreign relations / United States; Russia (Federation) / Foreign relations / Middle East; Middle East / Foreign relations / Russia (Federation); Concurrence internationale; États-Unis / Relations extérieures / Moyen-Orient; Moyen-Orient / Relations extérieures / États-Unis; Moyen-Orient / Relations extérieures / Chine; Moyen-Orient / Relations extérieures / Russie